2009
DOI: 10.1158/0008-5472.can-08-2753
|View full text |Cite
|
Sign up to set email alerts
|

C-1027, A Radiomimetic Enediyne Anticancer Drug, Preferentially Targets Hypoxic Cells

Abstract: The hypoxic nature of cells within solid tumors limits the efficacy of anticancer therapies such as ionizing radiation and conventional radiomimetics because their mechanisms require oxygen to induce lethal DNA breaks. For example, the conventional radiomimetic enediyne neocarzinostatin is 4-fold less cytotoxic to cells maintained in low oxygen (hypoxic) compared with normoxic conditions. By contrast, the enediyne C-1027 was nearly 3-fold more cytotoxic to hypoxic than to normoxic cells. Like other radiomimeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 32 publications
2
56
0
1
Order By: Relevance
“…LDM (C1027) also showed antiangiogenesis and antimetastatic activity, preferentially targeting hypoxic cells [14]. In the previous study, it has been studied for cancer treatment, enhancement of its targeting, selectivity and efficiency, and drug combination therapy of certain cancers [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LDM (C1027) also showed antiangiogenesis and antimetastatic activity, preferentially targeting hypoxic cells [14]. In the previous study, it has been studied for cancer treatment, enhancement of its targeting, selectivity and efficiency, and drug combination therapy of certain cancers [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…LDM also markedly inhibits the growth of transplantable tumors in vivo [11][12][13]. LDM has demonstrated unique characteristics in the treatment of cancer, such as preferentially targeting hypoxic cells, dosage-dependent regimens based upon p53 status, and high activity against multidrug-resistant cancer cells [14][15][16]. LDM is now in phase II clinical trials as a potential chemotherapeutic agent in China.…”
mentioning
confidence: 99%
“…In addition, the hypoxic nature of cells within solid tumors limits the efficacy of anticancer therapies, such as ionizing radiation and conventional radiomimetics, because their mechanisms of action require oxygen to induce lethal DNA breaks. Terry et al [30] reported that LDM could preferentially target hypoxic cells within tumors and overcome the radioresistance associated with poorly oxygenated cells. Therefore, anti-CD20 scFv-LDP-AE has the potential to overcome both the RTX-resistance and the radioresistance associated with poorly oxygenated cells in the treatment of B-cell NHL.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that treatment with C-1027 (Fig. 31) offers a facile approach for overcoming the radioresistance associated with poorly oxygenated cells [54].…”
Section: Enediyne Anticancer Drug C-1027mentioning
confidence: 99%